Econometric analysis of switching expectations in UK inflation* - Cornea-Madeira, A.; Madeira, J. (Oxford Bulletin of Economics and Statistics, 2022)
We estimate with UK data a Phillips curve model with backward-looking and forward-looking methods of determining inflation expectations and with agents switching between these based on their recent performance. We find that, while on average backward-looking and forward-looking methods have about equal weight, there are considerable movements in the weight given to each method. We show this model has better in-sample fit than other Phillips curve models and this is robust to the methodology chosen. The model out-of-sample forecasts on certain dates do better than other Phillips curve models and the Atkeson and Ohanian model.